The non-designer's Photoshop book essential imaging techniques for design - Williams, Robin 1953- (Peachpit Press, 2012)
Many designers and photographers own the entire suite of Adobe creative products, but they manage to learn only one or two of the applications really well. Robin Williams and John Tollett uses a series of individual exercises to teach image-editing tasks in Adobe Photoshop specifically to designers, who need to enhance their photos. Includes sections about Camera Raw and Puppet Warp features.--
Print version record
Keywords: Adobe Photoshop; Computer graphics; Image processing -- Digital techniques; Computer Graphics; Infographie; Traitement d'images; Techniques numériques; computer graphics; digital imaging; Image processing; Digital techniques